Digital transformation post-pandemic: A bibliographic research study (Research, Society and Development, 2025)
This article aims to investigate digital transformation in organizations in the post-pandemic context, analyzing how the adoption of digital technologies impacts organizational culture and human experience. The research seeks to understand the challenges and opportunities arising from this transformation, as well as to identify practices that can be adopted for effective implementation. To carry out this study, a bibliographic research methodology with a qualitative and exploratory approach was used. Through a review of relevant literature, sources such as books, academic articles, and dissertations discussing digital transformation and its implications in the labor market were analyzed. The results indicate that the COVID-19 pandemic accelerated the adoption of digital technologies, prompting companies to rethink their operations and prioritize organizational culture. A significant increase in e-commerce and a shift in consumer habits, with an emphasis on digital services, were observed. The research highlighted the importance of collaboration and innovation, showing that digital transformation should be seen as a multifaceted process that goes beyond technology. The conclusions suggest that digital transformation not only benefits organizations but can also have positive implications for society, promoting inclusion and accessibility. This article contributes to the academic understanding of digital transformation, providing valuable insights for organizational practice and the development of policies that favor a more inclusive and innovative future.